Morphological characterization of eggplant landraces: key for ensuring nutritional quality and biodiversity conservation - Martínez-Ispizua, Eva; Martínez-Cuenca, Mary-Rus; Marsal, José I.; Díez, María José; Soler, Salvador; Valcárcel, José Vicente; Calatayud, Ángeles (SEBP/SPFV, 2022)
The genetic erosion caused in crops by prioritizing production over quality has led to a loss of biodiversity (Brush, 1992; Castillo, 2008), which compromises global food security. As for eggplant, there is little morphological variability among commercialized eggplants (Hanson et al., 2006), and it is therefore necessary to have a source that helps to increase crop diversity, as are the landraces. Traditional varieties are those that have been differentiated by farmers through a historical process of selection, and are considered an important source of agricultural biodiversity (Jain & Gupta, 2013), which can be used for the development of new varieties while supporting the local economy (Ebbert, 2014).